Activist Board Games in Adult Education: Educational Philosophies, Learning Theories and Game Mechanics - Kamil M. Gerónimo-López (Adult Education Research Conference, 2023)
The use and design of activism board games in popular education are unexplored. This study explores the board game Rise-Up (TESA Collective, 2017). To gather data, game aesthetics were observed and analyzed. At least two issues are worth examining from an adult education lens, the operationalization of critical thinking and the relationship between educational goals and game mechanics.
Keywords: Activism; popular education; board games; radical aesthetics; critical thinking